Participant experiences of guided self-help Acceptance and Commitment Therapy for improving quality of life in muscle disease: a nested qualitative study within the ACTMus randomized controlled trial - Edwards, Victoria; Vari, Chiara; Rose, Michael; Graham, Christopher D.; O'Connell, Nicola; Taylor, Emma; McCracken, Lance M.; Radunovic, Aleksandar; Rakowicz, Wojtek; Norton, Sam; Chalder, Trudie (Frontiers in Psychology, 2023)
Introduction In adults, muscle disease (MD) is typically a chronic long-term condition that can lead to a reduced quality of life (QoL). Previous research suggests that a psychological intervention, in particular Acceptance and Commitment Therapy (ACT), may help improve QoL for individuals living with chronic conditions such as MD. Methods This nested qualitative study was incorporated within a randomized controlled trial which evaluated a guided self-help ACT intervention for people living with MD to explore their experiences of the intervention. Semi-structured interviews (n = 20) were conducted with those who had received ACT. Data were analyzed via thematic analysis. Results There were four overarching themes. (1) Views on whether therapy sessions would help with a medical condition: participants' expectations regarding ACT varied. Some participants were skeptical about mindfulness. (2) I was able to look at things in a different way: participants described increased meaningful activity, greater awareness of thoughts and emotions and acceptance or adaptation to mobility problems. Some described improvement in the quality of relationships and a sense of feeling free. (3) Treating the body and the mind together: following the intervention participants noted that a holistic approach to healthcare is beneficial. (4) Intervention delivery: The remote delivery was generally seen as helpful for practical reasons and allowed participants to speak openly. Participants voiced a need for follow-up sessions. Discussion Overall, the intervention was experienced as acceptable. Suggested improvements included de-emphasizing the role of mindfulness and adding follow-up sessions.